Hemoglobin-Derived Antioxidant Peptides from Beef Cattle in Ningxia: Identification Based on Computerized Screening and Molecular Docking - XU Feiran, WANG Yu, WANG Xiaojing, CUI Wei, WANG Yongkun, ZHOU Hui, WANG Zhaoming, CAI Kezhou, ZHANG Bao, XU Baocai (Shipin Kexue)
In this study, three enzymatic hydrolysis methods, alkaline protease (E1), pepsin + trypsin (E2), and alkaline protease + pepsin + trypsin (E3), were used to prepare hemoglobin hydrolysates from Ningxia beef cattle, which were screened for their antioxidant activity. Amino acid analysis and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were used to identify the amino acid compositions and sequences of the hydrolysates with molecular mass < 3 kDa. The potential antioxidant peptides were selected by computerized analysis and their activities were verified. Their action mechanism was studied by molecular simulation. The results showed that E3 exhibited the highest hydrolysis efficiency, and the < 3 kDa fraction obtained from the ultrafiltration of the resulting hydrolysate showed better antioxidant activity with half maximal inhibitory concentration (IC50) of (18.382 ± 0.023) mg/mL and (0.246 ± 0.012) mg/mL against 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cationic radical, respectively. The < 3 kDa fraction was rich in hydrophobic and aromatic amino acids, and four peptides with the best antioxidant activity were selected and identified, whose amino acid sequences were DWGHSW, VFYPW, GTGW and TYFPHF, respectively. Among them, VFYPW showed the highest DPPH radical and ABTS cationic radical scavenging capacity with IC50 of (0.350 ± 0.013) mg/mL and (9.482 ± 0.122) µg/mL, followed by DWGHSW. DWGHSW and VFYPW were found to form stable complexes with Keap1 protein (PDB ID: 2FLU) through hydrogen bonds and hydrophobic interactions. In summary, this study provides a theoretical basis for the application of hemoglobin peptides from Ningxia beef cattle as natural antioxidant supplements and contributes to the high-value utilization of blood resources from Ningxia beef cattle.